Legal Grounds of the Control System in Polish Public Administration - Hoffmann, Tomasz (Journal of Public Governance, 2009)
The present article undertakes the issue of the functioning of the control system of public administration in Poland. It explains the notion of control, the existing differences between inspection and supervision, and also with other forms of interference in the administrative activity. The author also defined the subject and the object of inspection, identified institutions exercising controlling power in the Polish legal system, divided and classified control. In the last part, the author focussed on the notion of audit and the resulting implications for the functioning of the Polish administration system itself. In particular, the controlling power exercised by courts was presented, with arguments supporting the thesis that these organs perform a controlling function.